التدفقات الدولية لرؤوس الأموال كمصدر للتمويل في ظل انخفاض اسعار البترول بالجزائر - بن زاير, عبد الوهاب; بن زاير, مبارك (جامعة الوادي - University of Eloued, 2017)
نفس نوعية الخط تأثر الاقتصاد الجزائري بشكل واضح بانخفاض أسعار البترول منذ منتصف سنة 2014، باعتبارها المصدر الرئيسي للتمويل، و لتجاوز هذه الازمة يسعى المشرفون على السياسة الاقتصادية بالجزائر الى استغلال مختلف البدائل المتاحة، و في ظل التفاعلات التي يشهدها العالم بين مختلف الكيانات الاقتصادية تعتبر التدفقات الدولية لرؤوس الاموال أداة مهمة يمكن الاعتماد عليها لتمويل النشاطات الاقتصادية. ضمن هذا الاطار تهدف هذه الدراسة الى تسليط الضوء على مدى استفاذة الاقتصاد الجزائري من التدفقات الدولية لرؤوس الاموال كمصدر للتمويل في ظل انخفاض اسعار البترول. Algeria's economy has been clearly affected by lower oil prices since mid-2014, as a major source of funding, to overcome this crisis, supervisors of economic policy in Algeria are trying to exploit the various alternatives available, in light of the global interactions among various economic entities, international capital flows are an important tool to finance economic activitie. Within this framework, this study aims to shed light the extent to which the Algerian economy has benefited from international capital flows as a source of funding in light of the low oil prices. .
International flows of capital as a source of financing in light of the low oil prices in Algeria
مقال
Keywords: اقتصاد ريعي،انخفاض أسعار البترول،مصادر تمويل، تدفقات دولية لرؤوس الأموال; Rentier economy, Low oil prices, Sources of funding, International